STUDI PERISTIWA POLITIK (PEMILIHAN UMUM INDONESIA TAHUN 2019) TERHADAP REAKSI HARGA SAHAM BLUECHIP DI INDONESIA - Rohani Rohani; Astuty Hasti (SEIKO : Journal of Management & Business, 2020)
This study aims to analyze the effect of political events in Indonesia as case studies on the 2019 general election and their reactions to the stock market in Indonesia. The event study approach is used in this research to observe abnormal returns on the blue-chip stock price index on the Indonesia Stock Exchange. The data in this study came from secondary data, namely data obtained from second parties. The secondary data in question was obtained from the Indonesia Stock Exchange in the form of data on the selling price of shares of the LQ 45 index which is a blue-chip issuer with a high level of liquidity on the Indonesia Stock Exchange in 2019. The observational data is grouped into two time periods consisting of the estimated period. and the event period (event window). The results show that there is a prolonged abnormal return that occurs before and after the 2019 general election and thus the market is considered inefficient in a semi-strong form based on the efficient market hypothesis Kata Kunci : Stock Market Reaction, Abnormal Return, Event Study, Country Risk, Saham Bluechip